Photography After Capitalism - Burbridge, Ben (Goldsmiths Press, 2023)
In Photography After Capitalism, Ben Burbridge makes the case for a radically expanded conception of photography, encompassing the types of labor too often obscured by black-boxed technologies, slick platform interfaces, and the compulsion to display lives to others. His lively and polemical analysis of today's vernacular photographic cultures shines new light on the hidden work of smartphone assembly teams, digital content moderators, Street View car drivers, Google “Scan-Ops,” low-paid gallery interns, homeless participant photographers, and the photo-sharing masses. Bringing together cultural criticism, social history, and political philosophy, Burbridge examines how representations of our photographic lives—in advertising, journalism, scholarship and, particularly, contemporary art—shape a sense of what photography is and the social relations that comprise it. More precisely, he focuses on how different critical and creative strategies—from the appropriation of social media imagery to performative traversals of the network, from documentaries about secretive manual labor to science fiction fantasies of future sabotage—affect our understanding of photography's interactions with political and economic systems.